(untitled) (Nexus International Journal of Science and Education, 2024)
This study examined the relationship between science identity and academic self-efficacy among junior high school students in Davao Oriental. Utilizing a quantitative-descriptive- correlational approach, the sample comprised 150 junior high school students who completed a survey. The findings revealed that the extent of science identity among the students was very high, indicating a solid identification and connection with the field of science. Additionally, the students exhibited high academic self-efficacy, suggesting a belief in their ability to succeed academically. Notably, the study also found a significant relationship between scienceidentity and academic self-efficacy, indicating that students’ confidence in their educational capabilities increased as they developed a stronger sense of identity in science. Specifically, science recognition emerged as the sole domain of science identity that significantly influenced academic self-efficacy, highlighting the importance of recognizing and valuing science-related achievements and contributions in fostering students’ confidence and belief in their intellectual abilities. These findings contribute to our understanding of the factors that shape students’ academic self-efficacy and emphasize the role of science identity in promoting academic confidence. The implications of these findings underscore the need for educational interventions and programs that foster science identity and recognize students’ accomplishments in the science field. Educators can enhance students’ academic self-efficacy and foster a positive attitude toward science education by cultivating a supportive and inclusive environment that promotes science recognition and identity development.